El espectáculo dramático-festivo del Corpus en la Salamanca del Renacimiento - Framiñán de Miguel, María Jesús (Madrid : Iberoamericana ; Frankfurt am Main : Vervuert, 2015)
This book traces the panorama of scenic, theatrical and musical activity that, according to its sources, took place in the city of Tormes during the 16th and first decade of 17th century on the occasion of the fun and festive Eucharistic celebration.
Incluye referencias bibliográficas.
Descripción basada en el editor de metadatos y otras fuentes.
Recurso electrónico. Santa Fe, Arg.: elibro, 2019. Disponible vía World Wide Web. El acceso puede estar limitado para las bibliotecas afiliadas a elibro.
Keywords: Corpus Christi Festival -- Spain -- Salamanca -- History -- 16th century; Corpus Christi Festival -- Spain -- Salamanca -- History -- 16th century -- Sources; Theater -- Spain -- Salamanca -- History -- 16th century; Theater -- Spain -- Salamanca -- History -- 16th century -- Sources; Festival de Corpus Christi -- España -- Salamanca -- Historia -- Siglo XVI -- Fuentes; Teatro -- España -- Salamanca -- Historia -- Siglo XVI -- Fuentes; Salamanca (Spain) -- Religious life and customs -- 16th century; Libros electronicos